2016
DOI: 10.17235/reed.2016.4600/2016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical status, quality of life, and work productivity in Crohn’s disease patients after one year of treatment with adalimumab

Abstract: Objective: Clinical trials have shown the efficacy of adalimumab in Crohn's disease, but the outcome in regular practice remains unknown. The aim of the study was to examine clinical status, quality of life, and work productivity of Crohn's disease patients receiving adalimumab for one year in the context of usual clinical practice.Material and methods: This was a prospective, observational study with a one-year follow-up. After baseline, Crohn's disease patients were evaluated at 1, 3, 6, 9, and 12 months aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Tumor necrosis factor (TNF) inhibitors, initially recommended only for patients with inadequate response to conventional therapy, are nowadays used earlier during the disease course, 1 sometimes in a topdown-approach, rather than step-up. 2 Clinical trials have evaluated the effects of TNF inhibitors on work productivity mainly by the Work Productivity and Activity Index [3][4][5][6][7][8][9][10] (Supplementary Table 1). Data from clinical trials have shown a decrease in patient-reported absenteeism during treatment with TNF-inhibitors [3][4][5][6][7]9,10 in selected populations with short follow-up (weeks or months).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor necrosis factor (TNF) inhibitors, initially recommended only for patients with inadequate response to conventional therapy, are nowadays used earlier during the disease course, 1 sometimes in a topdown-approach, rather than step-up. 2 Clinical trials have evaluated the effects of TNF inhibitors on work productivity mainly by the Work Productivity and Activity Index [3][4][5][6][7][8][9][10] (Supplementary Table 1). Data from clinical trials have shown a decrease in patient-reported absenteeism during treatment with TNF-inhibitors [3][4][5][6][7]9,10 in selected populations with short follow-up (weeks or months).…”
Section: Introductionmentioning
confidence: 99%
“…2 Clinical trials have evaluated the effects of TNF inhibitors on work productivity mainly by the Work Productivity and Activity Index [3][4][5][6][7][8][9][10] (Supplementary Table 1). Data from clinical trials have shown a decrease in patient-reported absenteeism during treatment with TNF-inhibitors [3][4][5][6][7]9,10 in selected populations with short follow-up (weeks or months). [3][4][5][6]8,9 However, the longterm effect of TNF-inhibitors in routine clinical practice is not known, and data on work ability during other treatments, including surgery, are sparse.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of Polish and foreign literature about Qol of CD patients is usually discussed by scientists representing medical fields, mainly in the specialization of gastrology and surgery. These studies, however, focus mainly on medical variables such as: type of treatment [28][29][30][31][32][33][34] surgical interventions [35][36] intestinal resections [37][38][39] or nutrition [40].…”
Section: The Literature and Researchmentioning
confidence: 99%
“…Clinically meaningful changes in mean SIBDQ total scores at week 24 were seen in naïve patients as well as in the subgroup of infliximab non-responders [ 57 ]. In clinical practice, Saro et al observed, in a prospective study with 126 CD patients, a significant increase in the IBDQ in the first year after starting adalimumab [56.7 (51.6–61.5) to 67.5 (60.1–73.6)] p < 0.05 [ 58 ].…”
Section: Quality Of Life Studies In CDmentioning
confidence: 99%